Hybrid computational intelligence challenges and applications - Bhattacharyya, Siddhartha 1975-; Snášel, Václav 1957-; Gupta, Deepak active 2015-2016; Khanna, A. S. (Academic Press, 2020)
Hybrid Computational Intelligence: Challenges and Utilities is a comprehensive resource that begins with the basics and main components of computational intelligence. It brings together many different aspects of the current research on HCI technologies, such as neural networks, support vector machines, fuzzy logic and evolutionary computation, while also covering a wide range of applications and implementation issues, from pattern recognition and system modeling, to intelligent control problems and biomedical applications. The book also explores the most widely used applications of hybrid computation as well as the history of their development. Each individual methodology provides hybrid systems with complementary reasoning and searching methods which allow the use of domain knowledge and empirical data to solve complex problems. Provides insights into the latest research trends in hybrid intelligent algorithms and architectures Focuses on the application of hybrid intelligent techniques for pattern mining and recognition, in big data analytics, and in human-computer interaction Features hybrid intelligent applications in biomedical engineering and healthcare informatics.
Includes bibliographical references and index. - Online resource; title from digital title page (viewed on April 21, 2020)
Keywords: Computational intelligence; Intelligence informatique; Livres numériques